Evidence that abrasion can govern snow kinetic friction - JAMES H. LEVER; SUSAN TAYLOR; GARRETT R. HOCH; CHARLES DAGHLIAN (Journal of Glaciology, 2019)
The long-accepted theory to explain why snow is slippery postulates self-lubrication: frictional heat from sliding melts and thereby lubricates the contacting snow grains. We recently published micro-scale interface observations that contradicted this explanation: contacting snow grains abraded and did not melt under a polyethylene slider, despite low friction values. Here we provide additional observational and theoretical evidence that abrasion can govern snow kinetic friction. We obtained coordinated infrared, visible-light and scanning-electron micrographs that confirm that the evolving shapes observed during our tribometer tests are contacting snow grains polished by abrasion, and that the wear particles can sinter together and fill the adjacent pore spaces. Furthermore, dry-contact abrasive wear reasonably predicts the evolution of snow-slider contact area, and sliding-heat-source theory confirms that contact temperatures would not reach 0°C during our tribometer tests. Importantly, published measurements of interface temperatures also indicate that melting did not occur during field tests on sleds and skis. Although prevailing theory anticipates a transition from dry to lubricated contact along a slider, we suggest that dry-contact abrasion and heat flow can prevent this transition from occurring for snow-friction scenarios of practical interest.